Role of diagnostic laparoscopy in patients with large cell neuroendocrine carcinoma of the ovary with cancerous peritonitis: case report and review of the literature - Hideaki Tsuyoshi; Kenji Yashiro; Shizuka Yamada; Makoto Yamamoto; Toshimichi Onuma; Tetsuji Kurokawa; Yoshio Yoshida (BMC, 2019)
Abstract Background Large cell neuroendocrine carcinoma is a very rare ovarian neoplasm that has a poor clinical outcome even in the early stage, and there is as yet no established treatment. Diagnostic laparoscopy has been used to determine the possibility of primary optimal cytoreductive surgery or neoadjuvant chemotherapy in patients with advanced epithelial ovarian cancer. However, the role of diagnostic laparoscopy is still unclear in large cell neuroendocrine carcinoma due to its rarity. Case presentation A 31-year-old woman with abdominal distention was referred to our hospital. She was strongly suspected of having advanced ovarian cancer because of a huge pelvic mass, massive ascites, and their appearance on medical imaging. However, cytological examinations from ascitic fluid by abdominal paracentesis did not show any malignant cells. She underwent diagnostic laparoscopy to evaluate the possibility of primary optimal cytoreductive surgery, and only tissue sampling was performed for pathological diagnosis because of the countless disseminated lesions of various sizes in the intraperitoneal organs. The patient had no postoperative complications, leading to the early start of postoperative chemotherapy. Conclusions To date, there have been no systematic reviews that focused on determining the treatment strategy using laparoscopy. Diagnostic laparoscopy can be helpful to determine the optimal treatment, including primary debulking surgery, neoadjuvant chemotherapy, or best supportive care, assisting in decision-making particularly for patients with advanced large cell neuroendocrine carcinoma with carcinomatous peritonitis.